The synthesis, characterization, removal of toxic metal ions and in vitro biological applications of a sulfanilamide–salicylic acid–formaldehyde terpolymer. Issue 60 (8th June 2016) - Vasanthakumar, V.; Saranya, A.; Raja, A.; Prakash, S.; Anbarasu, V.; Priya, P.; Raj, V.
Abstract : SASF terpolymer possess great applications for removal of heavy metal ions from environmental and industrial wastes. Abstract : A new terpolymer was synthesized by the polymerization of sulfanilamide, salicylic acid and formaldehyde (SASF) in the presence of glacial acetic acid as a catalyst. The characterization of the synthesized SASF terpolymer was conducted using various techniques such as elemental analysis, gel permeation chromatography (GPC), Fourier transform infrared (FTIR), ultraviolet-visible (UV-Vis), 1 H nuclear magnetic resonance (NMR), 13 C NMR, thermogravimetric analysis (TGA), X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive X-ray spectroscopy (EDX) measurements. The synthesized SASF terpolymer was used for the removal of Ni 2+, Cu 2+, Pb 2+, Cd 2+, Hg 2+ and Zn 2+ metal ions from aqueous solution. The effect of factors affecting the metal ion adsorption on the SASF terpolymer was studied as a function of the electrolytes in different concentrations, and the influence of pH in different ranges was studied using the batch equilibrium technique. The metal ion removal efficiency increased with an increase in the pH and concentration of the electrolytes. The maximum removal percentage was achieved at pH 6–7. Inductively coupled plasma-optical emission spectroscopy (ICP-OES) was employed for the determination of all metal ions. The in vitro antibacterial and anticancer activities of the SASF terpolymer were also investigated. The SASF terpolymer exhibited an effective antibacterial activity against Gram-positive methicillin-resistant Staphylococcus aureus, Bacillus subtilis and Gram-negative Salmonella typhi, Escherichia coli bacterial strains. The cytotoxicity studies indicated that the SASF terpolymer possesses much potential against the HeLa (mammalian cancer) cell line.